2011
DOI: 10.1007/s11046-011-9413-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antifungal Susceptibility Testing with Microdilution and Etest Methods of Candida Blood Isolates

Abstract: Candida species that show an increasing number of clinical and/or microbiological resistance to several antifungals and are the most common agents of invasive fungal infections. The aim of this study was to investigate the in vitro susceptibility of Candida blood isolates to antifungal agents (amphotericin B, fluconazole, itraconazole, and voriconazole) by comparative use of the CLSI reference microdilution method and Etest. Four hundred Candida blood isolates (215 Candida albicans, 185 non-albicans Candida st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…This observation is uncommon compared with almost all the previously reported studies that indicated some degree of sensitivity to amphotericin B. Although, in a study conducted by Ruan et al (2008), the resistance was extremely high against amphotericin B in C. krusei strains (95%) and in C. glabrata strains (53%), in recent years, the low rates of amphotericin B resistance have been reported in the C. albicans, C. glabrata, C. parapsilosis, C. tropicalis and C. krusei isolates (Metin et al, 2011;Taj-Aldeen et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…This observation is uncommon compared with almost all the previously reported studies that indicated some degree of sensitivity to amphotericin B. Although, in a study conducted by Ruan et al (2008), the resistance was extremely high against amphotericin B in C. krusei strains (95%) and in C. glabrata strains (53%), in recent years, the low rates of amphotericin B resistance have been reported in the C. albicans, C. glabrata, C. parapsilosis, C. tropicalis and C. krusei isolates (Metin et al, 2011;Taj-Aldeen et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, the overall EA between the CLSI and Etest RPMI agar was mostly >96% within the acceptable ±2 dilution range (1994 to 2011) for the most prevalent Candida species (C. albicans, C. glabrata, C. parapsilosis, and C. tropicalis) [30,31,[34][35][36] and C. neoformans [37] (Table 1). The exceptions were the lower percentages of EA in one study where the Etest data were evaluated at both 24 and 48 h versus the CLSI method [38], for various species, including C. lusitaniae and C. neoformans [30,39]. The Etest was also evaluated for testing C. krusei with amphotericin B with an acceptable EA [30,34].…”
Section: Amphotericin Bmentioning
confidence: 99%
“…The published EA percentages between both CLSI and Etest fluconazole MICs for six species of Candida and C. neoformans [31,34,35,[38][39][40][41][42][43] and the EUCAST [25,32] are presented in Table 3. Although the EA for fluconazole was >90% versus the Etest data for Candida spp.…”
Section: • Fluconazolementioning
confidence: 99%
“…Nevertheless, other Candida species have emerged as clinically important opportunistic pathogens (3)(4)(5)(6). Resistance to antifungal agents is becoming increasingly prevalent in Candida species (7). For example, C. lusitaniae, C. guilliermondii, and C. kefyr have been reported as resistant to amphotericin B (8).…”
Section: Introductionmentioning
confidence: 99%